2008
DOI: 10.1111/j.1551-2916.2008.02375.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of TiO2 Powders and Thin Films Prepared from Modified Titanium Alkoxide Precursors

Abstract: The modification of titanium alkoxides by chemical reactions with ligands yields complexes or molecular clusters that are substantially different from those of the parent alkoxides. In this study, we investigate the structural evolution of powders and thin films prepared from two titanium oxo‐alkoxyacylate clusters with different oxo‐core structures [Ti6(μ3‐O)2(μ2‐O)2](CH3COO)8(μ2‐OiPr)2(OiPr)6 and [Ti6(μ3‐O)6](μ‐RCOO)6(OiPr)6 ([6,4] and [6,6], respectively) as a function of annealing temperature. The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 64 publications
1
18
0
1
Order By: Relevance
“…The anatase to rutile transformation was reported to be a process of nucleation and growth 17,18 . Previous works suggested that the critical anatase crystallite size for anatase transforming to rutile ranges from 30 to 40 nm, 19,20 which is correspondent with the estimated crystallite size of T‐1 powder in this work. The XRD patterns show that T‐2 and T‐3 contain the pure anatase phase of TiO 2 .…”
Section: Resultssupporting
confidence: 81%
“…The anatase to rutile transformation was reported to be a process of nucleation and growth 17,18 . Previous works suggested that the critical anatase crystallite size for anatase transforming to rutile ranges from 30 to 40 nm, 19,20 which is correspondent with the estimated crystallite size of T‐1 powder in this work. The XRD patterns show that T‐2 and T‐3 contain the pure anatase phase of TiO 2 .…”
Section: Resultssupporting
confidence: 81%
“…The observed peak shapes for the annealed sample and the broadening in the as-deposited sample agree with spectra reported for anatase and amorphous TiO 2 in the literature. [35][36][37][38] The difference in electrical behavior of devices based on as-deposited versus annealed TiO 2 thin fi lms is due to the combination of changes in the oxygen content and in the structure of the fi lms upon annealing.…”
Section: Resultsmentioning
confidence: 99%
“…2(a) demonstrates that the crystallization is initiated at 400 C. The XRD pattern of TiO 2 thin lms annealed up to 300 C has a broad peak centered on 2q ¼ 26.5 , which may be assigned to the amorphous BSG substrate. 22 This observation leads to the inference that the titanium alkoxide did not result in the formation of titania up to an annealing temperature of 300 C. However, the spectrum for the lm annealed at 400 C exhibited a dramatic change with the appearance of a new Raman band centered around 635 cm À1 . Additional faint peaks at 2q ¼ 36.9 and 56.5 are also indentied as belonging to the (110) and (200) planes of anatase phase of TiO 2 (indexed according to the PCPDF le no.…”
Section: Resultsmentioning
confidence: 99%